2003
DOI: 10.1051/apido:2003002
|View full text |Cite
|
Sign up to set email alerts
|

Periodic mass flights of Apis laboriosa in Nepal

Abstract: -The investigations were conducted in the Himalayas in Nepal. Two cliff sites, one with 16 A. laboriosa nests and the other with 53 nests were observed. Together 120 periodic mass flights (PMF) performed by A. laboriosa worker bees during 8 days were recorded. Workers from 50-81% of colonies performed PMF, during days of adequate weather conditions. The flights were not performed during overcast days. Worker bees from different colonies perform PMF at different times of the day. Workers from the same colonies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 1 publication
0
20
0
1
Order By: Relevance
“…Description of MFAs in the giant honey bee, A. dorsata and A. laboriosa , mostly focused on the flight behavior, but there are two studies that reported an increased disorder and the occurrence of Dynamics of the bee curtain in Apis florea gaps in the bee curtain shortly before a MFA (Woyke et al 2003(Woyke et al , 2004. MFAs in A. florea and the giant honey bee species appear to be very similar with respect to flight behavior, but there might be differences in the initiation and preparation of the MFA due to differences in the organization of the curtain and the nest.…”
Section: Occurrence and Temporal Dynamics Of Mfamentioning
confidence: 99%
See 1 more Smart Citation
“…Description of MFAs in the giant honey bee, A. dorsata and A. laboriosa , mostly focused on the flight behavior, but there are two studies that reported an increased disorder and the occurrence of Dynamics of the bee curtain in Apis florea gaps in the bee curtain shortly before a MFA (Woyke et al 2003(Woyke et al , 2004. MFAs in A. florea and the giant honey bee species appear to be very similar with respect to flight behavior, but there might be differences in the initiation and preparation of the MFA due to differences in the organization of the curtain and the nest.…”
Section: Occurrence and Temporal Dynamics Of Mfamentioning
confidence: 99%
“…For instance, a number of different collective defensive movement patterns and sounds produced by the workers in the curtain have been reported (Kastberger et al 2011;Fuchs and Tautz 2011). In addition, a unique form of a short-lived Bmassed flight activity^(MFA) was observed in A. dorsata and A. laboriosa colonies, but the function of this behavior is still unclear (Batra 1996;Kastberger et al 1996;Woyke et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…laboriosa workers perform periodic mass flight during the day (Woyke et al, 2003a). They start those flights at 12 °C, when the workers perform AF.…”
Section: Abdomen Flipping Of Apis Laboriosa Workers During Different mentioning
confidence: 99%
“…and 1999 (see Tab. 2), Woyke et al 2001aWoyke et al , 2001bWoyke et al , 2003aWoyke et al , 2003bWoyke et al , 2004Woyke et al , 2005aWoyke et al 2005b Previously, the reason why a particular shape of comb or nest occurred was not explained. We provide what we believe is a logical explanalieve is a logical explanation for this phenomenon drawn on the basis of particular shapes of nests found in specific ambient conditions.…”
Section: Methodsmentioning
confidence: 99%